Hoek & Brown Collapse Criteria Method on The Road Section of Lende Tovea Village, Sirenja District, Donggala Regency - Muhammad Sarjan Djalil; Muslimin U. Botjing; Nunik Rezkiarti Janat (Postgraduate, University of Mataram, 2026)
Avalanches on public infrastructure such as highways occur unpredictable due to unstable slopes due to degraded rock material. Avalanches can potentially cause and material losses. The research was conducted to classify the rock mass with the Geological Strength Index (GSI) method as a parameter for determining the slope safety factor on the road section of Lende Tovea Village, Sirenja District, Donggala Regency, Central Sulawesi Province. To obtain the value of cohesion and angle of friction in the approach used Hoek & Brown collapse criteria. Determination of safety factor value using Spencer type method, using GeoStudio 2018 R2 software application. The slope on the road section of the research area is composed of igneous lithology in the form of rhyolite and diorite. Geological structures in the form of fracture and faults. The results showed that the slope of the road section in the northern part of Lende Tovea Village based​ on the Geological Strength Index (GSI) value in the range of 25-33 with the condition of the rock mass is in the category of very blockly, disturbed & poor and slicken with wedge avalanche type at observation stations 1-5. The results of the safety factors value at stations 1, 2, 4, and 5 are in a condition prone to landslides with values of 1.514; 1.482; 1.595; 1.408 respectively while at station 3 in a condition where landslides rarely occur with a value of 1.921.